PERLINDUNGAN HUKUM PENERIMA PINJAMAN TERKAIT BATASAN SUKU BUNGA PINJAMAN P2P LENDING - Brahmasta Lugas Prasetya (2022)
Regulation on loan interest rates in P2P Lending services that have not been regulated in POJK No.77/POJK.01/2016 concerning Information TechnologyBased Lending and Borrowing Services creates a legal vacuum and losses for loan recipients. The problem in this research is setting the limit on loan interest rates in the P2P Lending service which is only regulated in the AFPI Code of Conduct and the legal protection of the borrower regarding the limit on loan interest rates in the P2P Lending service. The research method used in this research is normative juridical research using a conceptual approach. This study found that setting the limit on loan interest rates in P2P Lending services regulated in the AFPI Code of Conduct has not provided legal certainty. In addition, the absence of rules for limiting loan interest rates in POJK No.77/POJK.01/2016 concerning Information Technology-Based Borrowing-Lending Services has not provided legal protection to loan recipients. To prevent losses suffered by loan recipients, the Financial Services Authority can make regulations on limiting interest rates for P2P Lending loans.